The Role of Students in Daily Activities with Santri of Madrasah Tasdiqiah, Songkla Province, Thailand - Muhammad Permadi; Atin Risnawati (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2026)
This study seeks to elucidate the function of KKN students as catalysts in enhancing religious values and fostering international relations. The international KKN program represents a distinctive community service model that emphasizes human resource development and cross-cultural social integration. This research focuses on the contributions of students from the Faculty of Islamic Studies at UNISMA Bekasi within service-oriented activities involving madrasah students and local communities in Thailand. This study employs a mixed-method approach, integrating qualitative and quantitative data within a descriptive framework. Data were collected through observation, documentation, and semi-structured interviews conducted with key informants, including KKN students, madrasah students, and members of the local community. The interviews explored participants’ perceptions of student roles, program effectiveness, and the impact on religious practices and intercultural interaction. The findings indicate that the active involvement of KKN students was positively received by both madrasah students and the local community. Interview results reveal that students played a significant role in strengthening religious understanding, promoting collaborative activities, and facilitating intercultural communication. These outcomes demonstrate that KKN students effectively functioned as catalysts in enhancing religious values and fostering international relations within the community context in Thailand.